Preliminary Evaluation of Guava (Psidium guajava L.) Tree Branches for Truss Fabrication in Nigeria (2006)
Some physical and mechanical properties of small diameter poles obtained from guava (Psidium guajava L) tree branches in relation to their potential use for truss fabrication were determined. The average green moisture content of wood from five replicate samples of debarked tree branches was 84%. The wood samples were naturally resistant to termite attack with and without the bark on. The mean oven-dry density of the wood samples was 674 kg/m3. This puts it in the density category of the preferred species for rafter and truss fabrication in Nigeria. The mean modulus of elasticity of the air-dried samples (at 50% moisture content) was 2829.1 N/mm2 while the corresponding mean modulus of rupture was 9.2 N/mm2. To evaluate the practicality of the proposition, a 2-metre, 4-web Pratt truss was designed and a prototype was successfully fabricated with the poles jointed with nailed plywood gusset plates.